An Analysis of Character Education in The Short Story of Malin Kundang - Diana; Tuminah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to determine the character education values articulated in the Malin Kundang short story using Abraham Maslow Hierarchy of Needs theory with the Narrative Policy Framework (NPF) Analysis Framework, focusing on 18 character education values described by the Ministry of Education. The method used in this research is a qualitative descriptive method. The main data source used in the story is Malin Kundang. The analysis results revealed significant differences in the realization of values between Malin Kundang and his mother, underscoring the idea that achieving material success without moral integrity can lead to personal destruction. The innovative application of Abraham Maslow theoretical framework reveals Malin Kundang's psychological conflict between pursuing social needs and family ties. At the same time, the NPF analysis explains how narrative components effectively convey character education values. The results showed 7 data points of character education values, namely Discipline, Hard Work, Independence, Curiosity, Religious, Responsibility, and Friendship/communicative. This research contributes to the study of literature and character education by establishing a theoretical framework for the analysis of folklore that serves as an effective medium for character education, as well as suggesting the advancement of balanced moral competence.